MATERNAL SATISFACTION WITH INTRAPARTUM CARE IN HEALTHCARE FACILITIES IN KERICHO COUNTY, KENYA - Chepkorir , Emily; Kipmerewo , Mary; Wanyonyi , Mable; John, Arudo (Journal of Health, Medicine and Nursing, 2021)
Purpose: The main objective was to determine maternal satisfaction with intrapartum care in healthcare facilities in the Kericho County and specifically to determine the association between mothers' experience of intrapartum care and satisfaction with quality of nursing, analyze the influence of psychosocial aspects on satisfaction with intrapartum care and evaluate the relationship between hospital factors and maternal satisfaction on intrapartum care among women delivering in healthcare facilities in Kericho County Materials and Methods: This was a cross sectional analytical research design and data was collected using mixed method approach. The study targeted women who delivered in the facilities used for study and 441 mothers were sampled. Data was analyzed using (SPSS) version 24. Descriptive statistics was used to describe the findings on socio-demographic characteristics and inferential statistics employed Chi square and logistic regression to determine maternal satisfaction with intrapartum care. Odds ratio was used to test the strength of association, and a p-value of â‰¤ 0.05 considered as statistically significant. Findings: Several factors influence mothers' satisfaction with intrapartum care. Employment (OR: 3.0; 95% CI: 1.2 - 7.4; p = 0.02) delivery through instrument/Caesarian section were 2.6 more likely to have been satisfied with the care unlike those who delivered through SVD (OR: 2.6; 95% CI: 1.1 - 6.0; p = 0.03). On the other hand, mothers who got encouragement and reassurance by midwives and doctors (OR: 0.2; 95% CI: 0.1 - 0.8; p = 0.02) were more likely to be satisfied with care. Mothers who were shown their babies immediately after delivery to identify sex of the baby (OR: 3.2; 95% CI: 1.5 - 7.0; p = 0.002) were 3 times more satisfied than their counterparts. Mothers who were asked for their opinion about unplanned procedure before it was performed (OR: 3.7; 95% CI: 1.1 - 12.6; p = 0.02) were four times more likely to be satisfied. In conclusion, determinants of intrapartum care satisfaction in public hospitals in the study area are: level of education, employment status and type of delivery, showing the baby to the mother immediately after delivery to identify sex, midwives and doctors asking clients their opinion about unplanned procedure before it is performed. Provision of linen and beds, provision of hot drinks and hot shower after delivery and provision of a locker are all associated with satisfaction. Unique Contribution to Theory, Practice and Policy: Therefore, the hospitals should allow mothers to stay with their birth companions and health care providers should be taught on importance of good relation and good communication skills.